Microglial responses to amyloid β peptide opsonization and indomethacin treatment - Leonard Brian; Mastroeni Diego; Kovelowski Carl J; Strohmeyer Ronald; Grover Andrew; Rogers Joseph (Journal of Neuroinflammation, 2005)
Abstract Background Recent studies have suggested that passive or active immunization with anti-amyloid β peptide (Aβ) antibodies may enhance microglial clearance of Aβ deposits from the brain. However, in a human clinical trial, several patients developed secondary inflammatory responses in brain that were sufficient to halt the study. Methods We have used an in vitro culture system to model the responses of microglia, derived from rapid autopsies of Alzheimer's disease patients, to Aβ deposits. Results Opsonization of the deposits with anti-Aβ IgG 6E10 enhanced microglial chemotaxis to and phagocytosis of Aβ, as well as exacerbated microglial secretion of the pro-inflammatory cytokines TNF-α and IL-6. Indomethacin, a common nonsteroidal anti-inflammatory drug (NSAID), had no effect on microglial chemotaxis or phagocytosis, but did significantly inhibit the enhanced production of IL-6 after Aβ opsonization. Conclusion These results are consistent with well known, differential NSAID actions on immune cell functions, and suggest that concurrent NSAID administration might serve as a useful adjunct to Aβ immunization, permitting unfettered clearance of Aβ while dampening secondary, inflammation-related adverse events.